Accelerated Cyanidation Assays Using LeachWELLÖ 60X - The Bannockburn Experience - Revy T (The Australasian Institute of Mining and Metallurgy, 1994)
A testwork program aimed to improve the assaying of underground face samples established that for an Accelerated Cyanidation Extraction using the LeachWELLTM 60X catalyst, followed by an Aqua Regia finish (to quantify non-cyanide-extractable gold): ò Assay results (including the aqua regia finish) from a full set of samples from one underground face can be returned within four hours. ò The reagent dose to make the method simple and 'bullet-proof' is 8 gm LeachWELLTM 60X and 20 gm NaCN per 200 gm sample (30 per cent solids). Pulverising is to 90 per cent passing 75 micron (compared to the standard of 90 per cent passing 150 micron), and cyanidation is completed within one hour - however both might be further optimised. ò The LeachWELLTM/Aqua Regia results demonstrate that Fire Assays suffer from a significant nugget effect which makes the Fire Assay data relatively unreliable. ò Original costs, specific to Bannockburn (viz including an Aqua Regia finish), handling approximately 20 000 to 25 000 per annum is estimated to be $5.40, ie about one-third less than fire assaying. Optimising is further reducing these costs. It is estimated that the LeachWELLT"'/Aqua Regia assay procedure has reduced the probable error limits of any given assay of this ore from the range 0.74x to 1.36x for Fire Assay, to an appreciably smaller range of 0.90x to 1.11x. Thus for a cut-off grade of 1.60 g Au/t, samples with Fire Assays ranging up to 2.18 g Au/t have 25 per cent chance of being below cut-off, while samples with Fire Assays as low as 1.18 g Au/t have an equal chance of actually exceeding cut-off grade. This 1 g Au/t range in uncertainty is generally unacceptable for many practicalgrade/tonnage relationships. By contrast, using LeachWELLTM + Aqua Regia assays, the estimated corresponding limits are 1.44 g Au/t and 1.78 g Auk respectively - a far more tolerable 0.34 g Au/t range of uncertainty. Subsequent data has demonstrated that sufficient accuracy for grade control is achieved by Accelerated Cyanidation alone, further halving the cost of assays.